Annual Research Review: Immersive virtual reality and digital applied gaming interventions for the treatment of mental health problems in children and young people: the need for rigorous treatment development and clinical evaluation. (2nd March 2021) - Halldorsson, Brynjar; Hill, Claire; Waite, Polly; Partridge, Kate; Freeman, Daniel; Creswell, Cathy
Abstract : Background: Mental health problems in children and young people are common and can lead to poor long‐term outcomes. Despite the availability of effective psychological interventions for mental health disorders, only a minority of affected children and young people access treatment. Digital interventions, such as applied games and virtual reality (VR), that target mental health problems in children and young people may hold a key to increasing access to, engagement with, and potentially the effectiveness of psychological treatments. To date, several applied games and VR interventions have been specifically developed for children and young people. This systematic review aims to identify and synthesize current data on the experience and effectiveness of applied games and VR for targeting mental health problems in children and young people (defined as average age of 18 years or below). Methods: Electronic systematic searches were conducted in Medline, PsycINFO, CINAHL, and Web of Science. Results: Nineteen studies were identified that examined nine applied games and two VR applications, and targeted symptoms of anxiety, depression, and phobias using both quantitative and qualitative methodologies. Existing evidence is at a very early stage and studies vary extensively in key methodological characteristics. For applied games, the most robust evidence is for adolescent depressive symptoms (medium clinical effect sizes). Insufficient research attention has been given to the efficacy of VR interventions in children and young people. Conclusions: The evidence to date is at a very early stage. Despite the enthusiasm for applied games and VR, existing interventions are limited in number and evidence of efficacy, and there is a clear need for further co‐design, development, and evaluation of applied games and VR before they are routinely offered as treatments for children and young people with mental health problems.